PROTECTIVE EFFECT OF ARJUNOLIC ACID (A NATURAL TRITERPENOID SAPONIN OF TERMINALIA ARJUNA (TA)ON ASPIRIN-INDUCED GASTRIC INJURY IN RATS: APOSSIBLE INVOLVEMENT OF INTERCELLULAR ADHESION MOLECULE-1 (ICAM-1) AND VASCULAR ENDOTHELIAL - IMAN O. SHERIF; AMAL A. HASSANIN (International Journal of Pharma and Bio Sciences, 2014)
The aim of this study is to investigate the effect of arjunolic acid in aspirin-induced gastric ulcer in rats.Twenty four male Sprague- Dawely rats were randomly allocated to four groups; the normal control, aspirin-induced ulceration, ranitidine, and arjunolic acid groups. All groups except the control and aspirin groups received pretreatment drugs for 14 consecutive days. On the 13th and 14th days, aspirin was administered orally to all groups except for control group. The gastroprotective effect of arjunolic acid was assessed by gastric mucosal determination of malondialdehyde, reduced glutathione, nitric oxide and expressions of cyclooxygenase-2, vascular endothelial growth factor (VEGF) and intercellular adhesion molecule-1 (ICAM-1). The changes in these parameters that are affected by aspirin-induced ulcer were corrected by arjunolic acid. Arjunolic acid has a protective effect against aspirin-induced gastric mucosal injury through attenuation of oxidative stress and upregulation of gastric VEGF expression with downregulation of ICAM-1expression.